UPGRADING OF TAYAN’S CRUDE BAUXITE USING ROTARY DRUM SCRUBBER - Husaini Husaini; Stefanus Suryo Cahyono; Retno Damayanti (Indonesian Mining Journal, 2014)
Indonesia has abundant bauxite resources at Tayan, West Kalimanatan, where the reserve is relied more than 800 million tons. There were two types of Tayan’s bauxite that have been used in the present research. One contains 34.63 % Al2O3 and 5.20 % reactive SiO2 which is known as low grade ore, while the second type contains 47.30 % Al2O3 and 5.79 % reactive SiO2 which is known as high grade ore. A Rotary Drum Scrubber (diameter 80 cm, length 200 cm, screen opening 2 mm) was applied to upgrade the crude bauxite ores. The research was started by crushing followed by scrubbing and screening. The scrubber is supported by water sprayer to achieve washed bauxite (+2mm of particle sizes) separated from tailing (-2mm of particle size). The researchs were conducted by varying the feed rate (300-2100 kg/hr), solid percentage (14-36%) and water flow rate (35-78 L/minute). The results show that feed rate and solid percentage have high impact to the quality of washed bauxite obtained. The higher is feed rate and solid percentage the lower is alumina content of the washed bauxite produced. An optimum condition is attained at1600 kg/hour of feeding rate, 25% solid and 8 minutes of residence time that is capable to produce washed bauxite with chemical composition of 45.25 % Al2O3 and 3.27 % reactive SiO2 (when the crude bauxite as the feed is low grade type). On the other hand, the washed bauxite obtained with chemical composition of 55.50 % Al2O3, 0.47 % reactive SiO2 and impurities content with particle sizes <2mm is approximately 2,1% (when the crude bauxite as the feed is typically high grade). The average increase of Al2O3 content in the washed bauxite is 6.63% and the average decrease of reactive SiO2 is 2.87%. The washed bauxite produced is reliable as feed material for Bayer process.